The Effect of Collaborative Strategic Reading (CSR) on Students' Reading Skills - Amalisa Ayu Safitri; Wahyu Diny Sujannah (IAIN Syekh Nurjati Cirebon, 2023)
Many studies have been conducted to show the effect of using Collaborative Strategic Reading (CSR) on students’ reading skills. However, CSR is rarely conducted in vocational high schools by using procedure text as the material. Therefore, this study aimed to determine the effect of CSR on students’ reading skills. This pre-experimental research involved 29 tenth-grade Hospitality students in the academic year 2023/2024 in one of the state vocational high schools in Malang. The pretest and posttest in the form of multiple-choice reading questions were administered to the students before and after the implementation of CSR. The findings revealed that the use of CSR was effective in improving students’ reading skills. Thus, it is recommended that English teachers apply CSR in teaching reading and give clear instructions on how to do it to the students. For future researchers, it is suggested that they conduct survey and interview to find out the students’ perspectives regarding the implementation of CSR to improve their reading skills.